HARKAT, DERAJAT, DAN MARTABAT WANITA DALAM ISLAM - Amir, Firman; Ade, Jufri (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
The study of gender from the perspective of Islamic history is an interesting study for academics to study, because there are many critical views that we can extract from original sources that explain gender studies, namely the Al-Qur'an and the Hadith of the Prophet Muhammad SAW. When gender issues become a public discourse, many things are imprinted in our minds, one of which is that there is still discrimination regarding women's rights to life, how women's true role must continue to receive fair treatment in all aspects of life, both in terms of economics, politics, culture, and from the other side. This is where we have to examine and truly understand how Islam views and explains women's rights. So that we don't get caught up in the thoughts of orientalists who often discredit discourse on Islamic studies, that Islam does not respect women's rights. So that we are not trapped in one-sided studies by Orientalists, there must be a clear and objective understanding of how the Al-Quran and Hadith of the Prophet Muhammad SAW explain women's rights or more clearly gender issues in Islamic history.